ANALISIS EFEKTIFITAS ANGGARAN SEBAGAI ALAT PENGENDALIAN DAN EVALUASI MANAJEMEN - Rahmat Hidayat; Slamet Riyanto; Bambang Libriantono (Universitas Tangerang Raya, 2022)
The need for implementation of activities and budget effectiveness must be carried out. This study uses a comparison of the adjustments from the budget results of KJPP Nanang Rahayu in 2010 to 2011 with their realization. Overall, the implementation of the budget as a control tool at KJPP Nanang Rahayu has been effective. However, the details of the budget have not been analyzed in detail by accountants. This means that management control for the budget is quite good.